An effective coaching model: The perceptions and strategies of professional team sport coaches and players in Australia - Bennie, A.; O'Connor, D. (International Journal of Sport & Health Science, 2011)
This paper explores professional coach and player perceptions of effective coaching, closely scrutinising what coaches do (behaviours) and what coaches think (perceptions). A unique range of professional coaches and players from Australian team sport contexts were observed and interviewed regarding the topic of effective coaching. Qualitative data analyses lead to the creation of an `Effective Coaching Model` (ECM) for professional sport with three major concepts that represent the professional coaches'/players' perceptions and strategies of effective coaching: (a) The Coach, (b) Coaching Skills, and (c) The Environment. After presenting the key features of the ECM and how they were applied in these professional contexts, the ECM is critiqued in relation to the various eminent models of sport coaching.